IMPLEMENTASI UNDANG-UNDANG NO. 3 TAHUN 1997 TENTANG PENGADILAN ANAK (Studi terhadap Anak yang Berhadapan dengan Hukum dalam Tingkat Penyidikan di Polres Purbalingga) - Mugiman Mugiman (Faculty of Law, Universitas Jenderal Soedirman, 2010)
In investigating a case involving child, the police always prioritized the child’s interest as the basis of handling the case and tried its best to avoid bringing the case to trial. The employed the penal and non penal approach. The non penal approach was done through diverting and restorative justice method. The diverting method was meant to eliminate the negative effect which might result from legal proceeding, and replaced it with a discretion which was based its function as public service provider. The police did this by aborting the legal process and returning the child to the parents or replacing with other form of obligation for the child to give social service. The impending factors in this implementation was that there had not been common perception among the police officers as the law enforcing body due to their lack of understanding of the spirit of the law. Besides that there was also the constraint due to lack of public service facilities and society’s lack of concern towards their neighborhood and tendency to judge child behavior as the same as that of the adults.Keywords : juvenile, penal approach, non penal approach